Practicing statistics by creating exercises for fellow students. (10th November 2015) - Bebermeier, Sarah; Reiss, Katharina
Summary: This article outlines the execution of a workshop in which students were encouraged to actively review the course contents on descriptive statistics by creating exercises for their fellow students. In a first‐year statistics course in psychology, 39 out of 155 students participated in the workshop. In a subsequent evaluation, the workshop was assessed as useful and appropriate to encourage students to practice statistics and to become prepared for the exam.